PROTOTYPE INTEGRASI APLIKASI MOBILE MIT APP INVENTOR DALAM MONITORING KINERJA BATERAI KENDARAAN SEPEDA MOTOR - Adi Putra, Haris; Yuliana, Putri; Saputra, Zanu; Dwi Yanti, Yus (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
As the number of vehicles in Indonesia increases, the need for battery monitoring systems becomes more crucial. This study develops a battery performance monitoring system for motorcycles integrated with a mobile application based on Mit app inventor. The system utilizes an ESP32 microcontroller along with voltage, current (INA219), and temperature (DS18B20) sensors to read battery parameters in real-time. The State of Charge (SoC) is calculated using a modified coulomb counting algorithm. An active protection feature using a relay is included to prevent overcharging, overcurrent, and short circuits. Test results show that under normal conditions, battery voltage ranges from 10.5V to 12.37V with an average load current of 233.4 mA. During a 30-minute charging process, the SoC increased by 10% with an average charging voltage of 14.97V. Data is displayed in real-time via an LCD and the mobile application, enabling users to efficiently monitor battery status and take preventive actions. This system enhances the reliability and safety of battery usage in motorcycles.